2020
DOI: 10.1002/adom.202000379
|View full text |Cite
|
Sign up to set email alerts
|

All‐Optical Helicity‐Dependent Switching in Hybrid Metal–Ferromagnet Thin Films

Abstract: Over the past decades, optical manipulation of magnetization by ultrafast laser pulses has attracted extensive interest. It not only shows intriguing fundamental science arising from the interactions between spins, electrons, phonons and photons, but also manifests the potential to process and store data at a speed that is three orders of magnitude faster than the current technologies. In this paper, we experimentally demonstrate all-optical helicity-dependent switching (AO-HDS) in hybrid metalferromagnet thin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 71 publications
(88 reference statements)
0
18
0
Order By: Relevance
“…demonstrated AO‐HDS with unpatterned Au capping layers over Ta 3/Pt 0.7/[Co 0.8/Pt 0.8] 3 /Ta 3 (in nm). [ 54 ] A minimum laser fluence of 3.01 mJ cm −2 was necessary to induce all‐optical switching with 50 nm thick Au layers compared to 0.296 mJ cm −2 in the ferromagnetic films without Au cladding. However, helicity dependence was observed over a wide fluence window spanning ≈10 mJ cm −2 in Au‐capped magnetic layers, while clear helicity‐dependent switching was not seen in bare films.…”
Section: Figurementioning
confidence: 99%
“…demonstrated AO‐HDS with unpatterned Au capping layers over Ta 3/Pt 0.7/[Co 0.8/Pt 0.8] 3 /Ta 3 (in nm). [ 54 ] A minimum laser fluence of 3.01 mJ cm −2 was necessary to induce all‐optical switching with 50 nm thick Au layers compared to 0.296 mJ cm −2 in the ferromagnetic films without Au cladding. However, helicity dependence was observed over a wide fluence window spanning ≈10 mJ cm −2 in Au‐capped magnetic layers, while clear helicity‐dependent switching was not seen in bare films.…”
Section: Figurementioning
confidence: 99%
“…Figure c, d , and e are reproduced with permission from ref. [ 116 ], Copyright (2020) WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim. Figure f is reproduced with permission from ref.…”
Section: All-optical Switching Of Ferromagnetic Materials and Nanostrmentioning
confidence: 99%
“…The result shows that the switching requires a minimal 0.15 ps duration of IFE field with an extreme value of around 20 T. Similar results were also found in FePt [ 112 , 115 ]. Recently, we found that the generated effective magnetic field can be prolonged in Co/Pt-Au heterostructures [ 116 , 117 ]. Based on the classic Lenz’s law, the decrease of the IFE-induced magnetic field wakes a loop current in the Au top-cladding layer.…”
Section: All-optical Switching Of Ferromagnetic Materials and Nanostrmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to the development of electronic devices toward miniaturization and high integration, optomagnetic and magnetoelectric materials are of growing interest in the fields of sensors and memory, where they allow control of the magnetization (or polarization) by an external field [1][2][3][4][5][6][7][8] . The charge, orbit, spin, and phonon are strongly coupled, endowing ferromagnetic materials with rich coupling properties, such as magnetoelectric coupling and optomagnetic coupling [9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%